Thermoelectric exhaust energy recovery with temperature control through heat pipes - Martins, Jorge (2011)
Currently, a great deal of the automotive industry’s R&D effort is focused on improving overall vehicle environmental and energy efficiency. For instance, one of the things that Electric Vehicles (EVs) and Hybrid cars (HEV) have in common is the recovery of waste energy, namely during braking. But, when an I.C. engine is operating (e. g. as a range extender in an EV), a large amount of energy is also wasted within the exhaust gases and with engine cooling, energy that could otherwise be recovered by different methods. This paper reports on the recovery of waste thermal energy using thermoelectric generators (TEG) for application in hybrid, extended range electric vehicles and more generally in any vehicle that could benefit from the generation of a small amount of electric current that would reduce the alternator operation time. Although some manufacturers are trying to develop TEGs to use at exhaust temperatures, there are still no commercially available TEG modules capable of withstanding these extreme temperatures. The present work assesses the potential of the use of heat pipes (HP) as a means of transferring energy from the hot exhaust gases to the TEG modules at a compatible temperature level while minimizing the loss of efficiency due to temperature downgrading. The type of HP used in this study is called Variable Conductance Heat Pipe (VCHP), and its deployment has the advantage of inducing good temperature control. Various types of HPs were designed, manufactured, tested and improved with the aim of enhancing the overall heat transfer process, enabling an optimal level of electric energy recovery from the referred TEG modules. This was accomplished by the testing of different fluids inside the HP and by regulating the pressure of the gas chamber. Although the system is still under improvement, the results indicate that the use of VCHPs in conjunction with thermoelectric generators is a convincing technique for recovering otherwise wasted energy from the exhaust gases.